Solve for g (g+7)/6=-48

Math
g+76=-48
Multiply both sides of the equation by 6.
6⋅g+76=6⋅-48
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6⋅g+76=6⋅-48
Rewrite the expression.
g+7=6⋅-48
g+7=6⋅-48
Multiply 6 by -48.
g+7=-288
g+7=-288
Move all terms not containing g to the right side of the equation.
Tap for more steps…
Subtract 7 from both sides of the equation.
g=-288-7
Subtract 7 from -288.
g=-295
g=-295
Solve for g (g+7)/6=-48

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top